FACTORS AFFECTING LOW DISTRIBUTION OF NEWSPAPERS IN THE MEDIA INDUSTRY; A CASE STUDY OF NATION MEDIA GROUP - KOECH, JOSEPHINE; Ombui, Mr. Kepha (European Journal of Business and Strategic Management, 2016)
Purpose: The purpose of this study was to investigate factors affecting low distribution of newspapers in the media industry; a case study of nation media group. Methodology: The study used a descriptive design. The instrument in use was the questionnaire which was issued to vendors, transporters and managers. The population were 3244 respondents comprised of all vendors in Nairobi who are 3,200, 22 transporters and 12 managers of Nation Media Group. The sample was 50 respondents. The study employed cluster and convenience sampling for vendors, systematic sampling to pick the transporters and managers. Convenience sampling was used to select vendors from each cluster due to the nature of work. The data collected was analyzed quantitatively using simple descriptive statistics such as frequencies and mean scores. Results: Results indicated that a majority of vendors agreed with the statement that change in customer's preferences, Competition from online distribution such as Facebook, twitter and online newspapers, Late delivery of newspapers, Pricing of newspapers, the newspapers are dropped off in a convenient place for me are the factors that lead to low distribution of newspapers. The results also revealed that a majority of transporters agreed with the statement that late printing of newspapers influence the distribution, bad condition of vehicles influence the distribution, dropping off newspapers in an inconvenient place for the vendors affects distribution, lack of security when and where they deliver newspapers affects distribution, Traffic jam affects the distribution of newspaper , long distances of where they deliver newspaper influence newspaper distribution are the factors that lead to low distribution of newspapers. This implies that the work is tiring and unsecured. The results further revealed that a majority of managers agreed with the statement that the transporting vehicles are not always in good condition to deliver newspapers, the newspapers are dropped off in an inconvenient place for the vendors, There is no security when delivering Newspapers, Traffic jam influence distribution of newspaper, Poor remuneration of transporters affect distribution , Poor work benefits of transporters affect distribution and Late production of newspapers affect distribution newspaper distribution are the factors that lead to low distribution of newspapers Unique contribution to theory, practice and policy It was recommended that there is need to enhance security for newspapers transporters. In this case the transporters would deliver the newspapers to vendors or pick from the sources in good time. The study would recommend that the sources of newspapers to reduce the pricing to sustain the business in market so as to encourage more entrepreneurs by inventing in the newspaper selling as long as it is profitable.